HUBUNGAN RENTAS SEMPADAN DAN PENGARUHNYA TERHADAP PEMBENTUKAN PEMIKIRAN HUKUM ISLAM DI KELANTAN (Cross-Border Relations and its Influence on Formation of Islamic Legal Thoughts in Kelantan) - Abd Rahman, Noor Naemah; Mohama Shukri, Mohamad Nabil (Journal of Al-Tamaddun, 2011)
The level of Islamic legal thought that exists in any society is very much influenced by the trends of education and legal thoughts applied therein. Such influences are often conformed to by the society, both the scholarly elites and the public. Based on this notion, this research seeks to understand the linkages existing between the trends of education and thoughts of Islamic jurisprudence, with special attention to the context of Kelantan. Historical analysis is used as a research approach. Observation shows the connection between legal thoughts scholars developed in their educational centers as well as the standards of legal thoughts constructed in this very society. Based on the historical evidences and facts, this research discusses four principal educational centers, each of which exercised a significant influence in the establishment of legal thought in Kelantan. These include scholars from al-Haramayn, Patani, Egypt and India. This paper also explains the linkages that existed between these four centers as well as the trends of education used in Kelantan, and the influence leading to the establishment of level of legal thoughts in the local society.